Перспективи поширення корпоративної соціальної відповідальності в систему державних закупівель - Олійник, О.О. (Економічні інновації, 2013)
В статті досліджено перспективи поширення корпоративної соціальної відповідальності в систему державних закупівель України. На основі досвіду зарубіжних країн розроблено схему впровадження рівня соціальної відповідальності підприємства в соціально-трудових відносинах в держзакупівлі. The paper deals with the expansion prospects of Corporate Social Responsibility (CSR) in public procurement (including sustainable procurement) in Ukraine. The analysis is based on the experience of foreign practitioners and describes a concept whereby contracting authorities integrate social and environmental concerns in their public procurement activity.